2008
DOI: 10.1300/j069v27n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Symptomatology and Healthcare Utilization in HIV/HCV Co-Infected Drug Users in Miami

Abstract: HIV/HCV co-infection is becoming one of the main causes of death in HIV+ persons. We determined quality of life, clinical symptoms and health care utilization in HIV mono-infected and HIV/HCV co-infected chronic drug users. After consenting 218 HIV+ drug users, a physical examination and questionnaires on demographics, quality of life, drugs of abuse, and healthcare utilization were completed. Blood was drawn for HCV status, CD4 cell count, HIV viral load, CBC and chemistry. HIV/HCV co-infected participants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
5
24
0
1
Order By: Relevance
“…Consistent with our prediction, and supporting previous literature (Baum et al, 2008;Braitstein et al, 2005), our findings indicated that co-infected patients exhibited lower QoL in the four QoL domains, compared to patients with HIV only. Our findings also partially agree with prior studies that found reduced physical QoL among co-infected patients compared to patients with HIV only (Tsui et al, 2007) and that co-infection with HCV is related to lower mental health scores (Briongos Figuero et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our prediction, and supporting previous literature (Baum et al, 2008;Braitstein et al, 2005), our findings indicated that co-infected patients exhibited lower QoL in the four QoL domains, compared to patients with HIV only. Our findings also partially agree with prior studies that found reduced physical QoL among co-infected patients compared to patients with HIV only (Tsui et al, 2007) and that co-infection with HCV is related to lower mental health scores (Briongos Figuero et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Despite this expectation, the literature contains inconsistent findings regarding the QoL of HIV/HCV patients. These mixed findings include studies that have reported that QoL is decreased in co-infected patients compared to HIV mono-infected patients (Baum et al, 2008), that only physical aspects of QoL are decreased in co-infected patients compared to mono-infected patients 4 (Tsui et al, 2007), and that QoL in co-infected patients is decreased compared only to controls and not compared to HIV-negative or HCV-negative mono-infected patients (Fleming et al, 2004). Other studies did not find significant differences in QoL between HIV/HCV patients and HIV or HCV mono-infected patients Pantalone et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis C co-infection was not associated with depression in multivariable analyses in our study, but has been independently prognostic of depression in other HIV cohorts. 51,52 We performed separate analyses by sex to elucidate factors associated with the high rates of depression in women. While Hispanics and non-Hispanic blacks were more likely to be depressed overall, Hispanic women had the highest rates of depression (as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…No caso relatado neste artigo, o paciente apresentava sorologia positiva ao HIV e ao HCV. Na literatura, encontram-se diversas referências ao impacto que o diagnóstico de infecção pelo HIV causa no estado mental, desde transtornos de ajustamento a alterações cognitivas [7][8] . Também é reconhecido o impacto do tratamento para hepatite C no humor dos pacientes, como no caso citado, no qual interferon foi a droga escolhida, que tipicamente causa humor disfórico ou depressivo 9 .…”
Section: Comentáriosunclassified